4D Bioprinting, Newer Prospects in Regeneration - Utkalika Das1, Gatha Mohanty2, Rashmita Nayak3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The new concept which has come up in recent timesbeing integrated with 3D bioprinting is 4-dimensionalbio-printing. This is now considered the most appropriate solution for “tissue engineering”. It has thepotential to construct functional structure and also fabricate 3D patterns of biological architecture whichcan change shape under various stimuli by use of “stimulate responsive material”. 4Dbio-printing providesa great potential for tissue engineering of bone. The properties like shape memory of the printed structureis used for repair of personalized bone defect and the properties such as functional maturation helps inpromoting osteogenic differentiation of stem cells. This review aims to discuss the concept of 4D bioprintingand its application in “bone tissue engineering”.